SAE Technical Paper Series 2013
DOI: 10.4271/2013-01-2195
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Coanda Effect

Abstract: This paper presents a theoretical model of Coanda attachment mechanisms and laws of the Coanda effect. In this paper, it has been considered a very conventional setup in order to define by a theoretical analysis a mathematical model of the Coanda adhesion. It has been produced a complete mathematical model which could allow simple engineering calculations through an effective solutions of the differential equations of the system. A parametric model has defined as a function of main cinematic and geometric para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…and n = 7 allows good results for the Coanda effect at the wall, as supported also by the work of Pope and Pelfrey [17,18] for the mathematical modeling of generalized turbulent flows, with particular reference to the flat plane flow equations and the turbulent curved jets, as reports Trancossi [19]. Trancossi [11] demonstrated that with the hypothesis of moderate wall curvature (i.e., the curvature ratio = ℎ ≪ 1) the boundary layer analysis is close to the flat plate case. So, defining a proper Reynolds number, relative to the outflow on the convex wall:…”
Section: It Holdsmentioning
confidence: 68%
See 2 more Smart Citations
“…and n = 7 allows good results for the Coanda effect at the wall, as supported also by the work of Pope and Pelfrey [17,18] for the mathematical modeling of generalized turbulent flows, with particular reference to the flat plane flow equations and the turbulent curved jets, as reports Trancossi [19]. Trancossi [11] demonstrated that with the hypothesis of moderate wall curvature (i.e., the curvature ratio = ℎ ≪ 1) the boundary layer analysis is close to the flat plate case. So, defining a proper Reynolds number, relative to the outflow on the convex wall:…”
Section: It Holdsmentioning
confidence: 68%
“…Trancossi [11] demonstrated that with the hypothesis of moderate wall curvature (i.e., the curvature ratio C r = h R c 1) the boundary layer analysis is close to the flat plate case. So, defining a proper Reynolds number, relative to the outflow on the convex wall:…”
Section: It Holdsmentioning
confidence: 88%
See 1 more Smart Citation
“…Dragan [11] has independently validated the preliminary Coanda effect model by Trancossi and Trancossi and Dumas. A general overview has been produced by Dumas et al [12] 1.3 Coanda effect modelling Significant research activity has been conducted on Coanda effect modelling and analysis. In particular, Trancossi, Dumas et al [13] produced a theoretical model of Coanda attachment mechanisms and the laws of the Coanda effect. The proposed model has been realized by integration of Navier Stokes equations starting from the Dragan [14] model.…”
Section: Acheon Nozzle Architecturementioning
confidence: 99%
“…investigated [11] and a preliminary analysis of the Coanda adhesion based on a simplified exact integration of Navier-Stokes equation under a set of simplified hypothesis [12] has produced. After these results, it has been possible to obtain an effective model of the nozzle using Bernoulli theorem integral equations and the inviscid irrotational flow hypothesis by Bradshaw [13].…”
Section: Incas Bulletin Volume 6 Issue 1/ 2014mentioning
confidence: 99%